Experimental Investigation of shear characteristics and failure in sandwich beams with cores comprising steel hollow sphere assemblies - Yiatros, Stylianos; Marangos, Orestes; Brennan, Feargal P. (My University, 2019)
Metal foam sandwich components are novel metallic composites that can offer advantages in bucking mitigation and vibration damping at low weight. Assemblies of metallic hollow spheres, bonded together with thermosetting epoxy and acting as core material in sandwich components, can be easily fabricated and potentially work as multifunctional buckling stiffeners and passive dampers. The work herein presents experimental work undertaken during a Marie Curie Fellowship at Cranfield University in the UK and subsequent analysis undertaken at CUT in Cyprus to determine the shear characteristics of this versatile composite material. Two types of steel sphere cores were examined, based on the distribution of sphere sizes. SFS4 refers to assemblies comprising spheres of the same diameter in 3 layers, while SFSGRD refers to assemblies comprising two sizes of spheres, in three layers, where the smaller sphere sizes (and hence denser layers) were closer to the face plates. The specimens were primarily under monotonic 4-point testing while cyclic 4-point bending was also undertaken to capture the fatigue response of these assemblies as sandwich cores. Displacement fields, crack initiation and propagation were captured via a DIC system during the monotonic tests so that failure characteristics and post-failure residual stiffness and strength were identified, measured and recorded. Shear parameters were extracted via statistical analysis from the results, exhibiting good correlation between specimens of the same type as well as marking the distinct merits of each core stratification.
Keywords: Metal foam sandwich; Sandwich components